Evaluation of the Effect of Wheat Germ Oil and Olmutinib on the Thioacetamide-Induced Liver and Kidney Toxicity in Mice - Salman Alamery; Seema Zargar; Fatimah Yaseen; Tanveer A. Wani; Abdulaziz Siyal (Life, 2022)
Thioacetamide (TAA) intoxication produces a reproducible standard animal model of induced liver and kidney injuries where free radicals are produced by phase I oxidation reactions, which eventually leads to liver and kidney failure. Wheat germ oil (WGO) is a unique food supplement with concentrated nutrient efficiency and has remarkable antioxidant functions. Olmutinib, on the other hand, is a chemotherapy drug considered safe for kidneys and the liver. Therefore, in this study, WGO and olmutinib were investigated for their effect on TAA-induced liver and kidney damage. Inflammatory markers; interleukin-1 beta (IL-1β); IL-6; and the levels of enzymatic markers ALT (Alanine aminotransferase), AST (Aspartate aminotransferase), LDH (Lactate dehydrogenase), and CK (creatinine kinase) in serum for liver and kidney were analyzed and evaluated along with histopathological changes in the tissue. Thirty male mice 4–6 weeks of age were grouped into five groups of six animals: the control group (saline) and the other groups (Groups II to V), which were given thioacetamide for two weeks. In addition, Group II continued with TAA; Group III was given olmutinib (30 mg/kg), Group IV was given the wheat germ oil (WGO) (1400 mg/kg), and Group V was given (olmutinib (30 mg/kg) + WGO (1400 mg/kg)) for five days. The results suggested that olmutinib treatment potentiated TAA-induced liver and kidney injury. At the same time, WGO efficiently alleviated TAA and TAA–olmutinib toxicity in Groups IV and V. The histological studies also showed reduced damage with WGO in the animal model. Hence, it was concluded that WGO could significantly reduce liver and kidney damage caused by TAA and olmutinib in mice.